Taking sides: translators and journalists in the Spanish civil war. - Rodríguez-Espinosa, Marcos (SAGE, 2022)
Soon after the uprising of General Franco in July 1936, the elite of international journalism turned its attention to the political undercurrents of the emerging Spanish Civil War, a historical period which would become a ‘golden age’ for foreign correspondents, and a conflict where women would for the first time play a leading role in global war reporting. Their battlefield accounts often reflect a biased understanding of the ideological confrontation of the two warring factions. For many foreign journalists, sending their chronicles back home meant paying a heavy toll, since correspondents were only allowed on the frontline when accredited and any journalist held prisoner could easily be mistaken for a spy. Drawing on a selection of historical, journalistic, media and translation studies research sources, as well as on a number of memoirs, personal accounts and biographies, in this article we discuss some up to now uncharted issues arising from the symbiotic connection between translation and journalism during the Spanish CivilWar: (a) their lack of proficiency in Spanish and their unfamiliarity with the country made it necessary for many correspondents to rely on the assistance of interpreters, fixers, guides and press officers, recruited for their ideological commitment to the rebel military uprising or to the Republican Government; (b) the role of translation in the Press and Propaganda Offices set up by the incipient Nationalist government, the Spanish Republic and the Catalan and Basque autonomous governments; and (c) the complex relationship between foreign correspondents and translators working for the censorship departments set up by Francoist and Republican Press Offices in order to prevent journalists from revealing information which might undermine the morale of civilians or troops, and the international reception of the narratives they sought to disseminate abroad.
Política de acceso abierto tomada de: https://v2.sherpa.ac.uk/id/publication/9362
Keywords: España - Historia - 1936-1939 (Guerra civil); Periodismo - Traducción; Journalistic translation research; History of translation; Translation and conflict; Spanish civil war; Censorship and propaganda